DAKWAH ONLINE PADA MASYARAKAT PERKOTAAN (Suatu kajian kemanfaatan) - Fatimah, Fatimah; kamridah, kamridah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2024)
This research aims to determine the social reality of urban communities in utilizing digital platforms which focuses on the use of Facebook as a medium for da'wah. The focus of this research study discusses online da'wah in urban communities, a study of benefits as an ethical principle in Islamic journalism. The benefit intended in this paper is a study of da'wah targets who use the Facebook application to access da'wah material. This type of research is qualitative with a communication science and da'wah approach. Data collection techniques through observation and interviews using content analysis. Urban communities respond well to the use of Facebook on social media platforms in online da'wah. It is very easy for people who use smartphones to access preaching materials according to Mad'u's needs. The use of Facebook as a social media platform is supported by the availability of an adequate internet network. Online Da'wah is a new construction of da'wah with the use of new media as a development of digital technology. The challenges of Online Da'wah can be seen in the aspects: connection, content, context and contact. Abstrak Penelitian ini bertujuan untuk mengetahui realitas sosial masyarakat Perkotaan dalam memanfaatkan platform digital yang difokuskan pada penggunaan facebook sebagai media dakwah. Fokus kajian penelitian ini membahas tentang dakwah online pada Masyarakat perkotaan suatu kajian kemanfaatan sebagai prinsip etika dalam jurnalistik Islam. Kemanfaatan yang dimaksudkan dalam tulisan ini adalah kajian tentang sasaran dakwah yang menggunakan aplikasi facebook dalam mengakses materi dakwah. Jenis penelitian ini adalah kualitatif dengan pendekatan ilmu komunikasi dan dakwah. Teknik pengumpulan data melalui observasi dan wawancara dengan menggunakan content analisys. Masyarakat Perkotaan merespon baik adanya pemanfaatan facebook pada platform media sosial dalam dakwah online. Masyarakat pengguna smartphone sangat mudah mengakses materi dakwah sesuai dengan kebutuhan mad’u. Penggunaan Facebook sebagai Platform media sosial didukung dengan ketersediaan jaringan internet yang memadai. Dakwah Online merupakan dakwah konstruksi baru dengan pemanfaatan new media sebagai perkembangan teknologi digital. Tantangan Dakwah Online dapat dilihat dalam aspek: connection, content, context dan contact.